A Satellite Survey of Cloud Cover and Water Vapor in the Southwestern USA and Northern Mexico. (13th February 2017) - Carrasco, E.; Avila, R.; Erasmus, A.; Djorgovski, S. G.; Walker, A. R.; Blum, R.
Abstract: Cloud cover and water vapor conditions in the southwestern USA and northern Mexico were surveyed as a preparatory work for the Thirty Meter Telescope (TMT) in situ site testing program. Although the telescope site is already selected, the TMT site testing team decided to make public these results for its usefulness for the community. Using 58 months of meteorological satellite observations between 1993 July and 1999 September, different atmospheric parameters were quantified from data of the 10.7 μ m and of 6.7 μ m windows. In particular, cloud cover and water vapor conditions were identified in preferred areas. As a result of the aerial analysis, 15 sites of existing and potential telescope were selected, compared, and ranked in terms of their observing quality. The clearest sites are located along the spine of the Baja peninsula and into southern California on mountain peaks above the temperature inversion layer. A steep gradient of cloudiness was observed along the coast where coastal cloud and fog are trapped below the inversion layer. Moving from west to east over the continent, a significant increase in cloudiness was observed. The analysis shows that San Pedro Mártir, San Gorgonio Mountain and San Jacinto Peak have the largest fraction of clear sky conditions (∼74%). The site with the optimal combination of clear skies and low precipitable water vapor is Boundary Peak, Nevada. An approach based in satellite data provided a reliable method for sites comparison.